2020
DOI: 10.1007/s42535-020-00159-w
|View full text |Cite
|
Sign up to set email alerts
|

Indole acetic acid (IAA) producing endophytic bacteria on direct somatic embryogenesis and plant regeneration of Exacum travancoricum Bedd.

Abstract: Endophytic bacteria were isolated from Withania somnifera (L.) Dunal and their potentials were explored through the in vitro plant regeneration techniques. Initially, indole acetic acid (IAA), phosphate solubilization and siderophore producing isolates were screened out. These isolates were identified using molecular tools like 16s rRNA gene sequences namely Bacillus pumilus AS02, Sphingobacterium thalpophilum AS34, Pseudomonas aeruginosa AS36, Agrobacterium tumefaciens AS38 and Enterobacter aerogenes AS75. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Except for K. cowanii, which is considered to be from clinical origin, other species of the genus are nitrogen-fixing bacteria, which are commonly associated with plants (Li Y. et al, 2017). They are most frequently found in the nitrogen-fixing bacterial community of some non-leguminous plant, such as rice (Hardoim et al, 2013) and sugarcane (Raju et al, 2020). The Kosakonia species contains flagella, which enable them to swim and possibly help in the attachment to the plant surface.…”
Section: Discussionmentioning
confidence: 99%
“…Except for K. cowanii, which is considered to be from clinical origin, other species of the genus are nitrogen-fixing bacteria, which are commonly associated with plants (Li Y. et al, 2017). They are most frequently found in the nitrogen-fixing bacterial community of some non-leguminous plant, such as rice (Hardoim et al, 2013) and sugarcane (Raju et al, 2020). The Kosakonia species contains flagella, which enable them to swim and possibly help in the attachment to the plant surface.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizosphere bacteria have the ability to produce the phytohormones that play important roles in processes such as cell division in symbiotic as well as non-symbiotic plant roots [51]. Phytohormones are mainly classified as gibberellins, cytokinins, ethylene and auxins that affect plant-microbe associations [52,53].…”
Section: Production Of Phytohormonementioning
confidence: 99%
“…The microbial phytohormones stimulate plant development and enhance plant tolerance to abiotic and biotic stresses [35,56]. Moreover, previous studies have reported that phytohormones stimulate the innate immunity of plants against pathogens such as bacteria and fungi [18,51,57]. Kapoor et al [58] reported the inhibition of Verticillium dahliae and Fusarium oxysporum growth and development by up to 70% by an IAA-producing endophytic fungi.…”
Section: Production Of Phytohormonementioning
confidence: 99%
“…Bacterial synthesis of IAA is associated with root proliferation when the released IAA quantity is optimum for the associated plant species. However, the positive effects of bacteria-produced IAA on plant phenotype are seen only in conjunction with other PGP mechanisms [ 161 , 162 , 163 , 164 ], but bacteria-producing IAA might confer a significant advantage to plants in Hg phytoremediation field situations because it stimulates rooting. NH 3 production is often associated with N 2 -fixing bacteria.…”
Section: Microorganisms-assisted Hg Phytoremediationmentioning
confidence: 99%